2011
DOI: 10.1128/iai.01071-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Kinetics ofEscherichia coli- andStaphylococcus aureus-Specific Activation of Key Immune Pathways in Mammary Epithelial Cells Demonstrates ThatS. aureusElicits a Delayed Response Dominated by Interleukin-6 (IL-6) but Not by IL-1A or Tumor Necrosis Factor Alpha

Abstract: Infections of the udder by Escherichia coli very often elicit acute inflammation, while Staphylococcus aureus infections tend to cause mild, subclinical inflammation and persistent infections. The molecular causes underlying the different disease patterns are poorly understood. We therefore profiled the kinetics and extents of global changes in the transcriptome of primary bovine mammary epithelial cells (MEC) after challenging them with heat-inactivated preparations of E. coli or S. aureus pathogens. E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
188
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(211 citation statements)
references
References 57 publications
18
188
3
2
Order By: Relevance
“…However, one study did not detect any IL-1b (34), whereas another claims that S. aureus does not induce TNF (35). Most studies on S. aureus have been done using the isolated cell-wall components peptidoglycan and LTA, rather than whole bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study did not detect any IL-1b (34), whereas another claims that S. aureus does not induce TNF (35). Most studies on S. aureus have been done using the isolated cell-wall components peptidoglycan and LTA, rather than whole bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Identical results were reported previously for il1a (22,34), tnfa (22,26,29,31,56), and il1b (26, 29 -31, 34, 52, 56). On the contrary, Günther et al (24) showed an upregulation of il6 but not of il1a and tnfa in MEC stimulated by heat-inactivated S. aureus. The genes encoding nfkbia, nfkbiz, and rela were upregulated in cells treated with Sa and Sp, respectively.…”
Section: Mec Responses To Live S Aureus or Bacterial Supernatantmentioning
confidence: 97%
“…To offset part of these issues, in vitro models of MEC cultures have been largely used to study the interaction of Escherichia coli or S. aureus with the host cells (11,22,25,29,52,58). Although the interaction of MEC with live bacteria has already been studied in several reports (29,31,34), heat-killed bacteria (22)(23)(24)(25) and pathogen-associated molecular patterns (PAMP), such as lipopolysaccharide (LPS) for E. coli or lipoteichoic acid (LTA) for S. aureus (1,11,13,30,37,41,58) or supernatant (Sp) (34), are more commonly used. The recourse to synthetic or inert stimuli avoids bacterial development in the culture medium and ensuing consumption of nutrients by the bacteria or release of highly toxic compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Si les approches classiques fondées sur l'étude des réponses à l'infection ne donnent pas de résultats satisfaisants, sur quelles connaissances peut-on fonder de nouvelles approches ? Les recherches sur le système immunitaire inné de la mamelle des ruminants ont fourni des connaissances assez développées (Aitken et al, 2011, Rainard & Riollet, 2006, et ce domaine de recherche reste actif, notamment en ce qui concerne la contribution des cellules épithéliales mammaires (Gilbert et al, 2013, Günther et al, 2011. En comparaison, les recherches sur l'immunité mammaire adaptative à médiation cellulaire, après avoir fait l'objet d'assez nombreuses études dans les années 1980-1990, sont pratiquement au point mort, et restent très lacunaires.…”
Section: Nouvelles Approches Permises Par Les Avancées Conceptuelles unclassified